Bad Hair Day?: A Guide to Dealing with Everyday Stress - Scott-Cameron, Nancy (Element Children's Books, 2000)
Offers advice to young adults on how to deal with stress at school and home, and includes mental and physical exercises designed to relieve tension.
Keywords: Juvenile literature-Emotions (Stress)-Non-fiction